Carios Babad Sumedang - Dede Burhanudin (Center for Research and Development of Religious Literature and Heritage, Agency for Research and Development and Training, Ministry of Religious Affairs of the Republic of Indonesia, 2012)
This article deals with Prince Gesan Ulun of Sumedang Larang kingdom. It is said that in his journey of seeking knowledge in Demak and Cirebon, the prince felt in love with Haris Baya, the queen of Girilaya Kingdom of Cirebon. This led to bloody conflicts between Cirebon and Sumedang Larang. Thanks to the advice of Mataram ruler, the conflict eventually came to an end. The advice was based on Islamic teachings. Gesan Ulum married Haris Baya. But he had to relinguish some of his territory to Cirebon